Climate change impacts on high rise buildings - Maa, Han Long (2016)
The changing climate in the future due to global warming will have an impact on the buildings in Singapore. The climatic factors which include wind and precipitation will be likely to increase in the future. This will cause an effect on the design loadings that are used in the building code to design for the building. Current buildings that use past building code that is designed based on historical climate data might not be able to sustain in the future when climate changes. Therefore, this study presents the calculations and an investigation into the relevance of the different climate change scenarios which include the wind and rainfall that are factored as the design loadings on buildings. A case study on the research paper done for the Netherlands current building code based on current wind velocity and rainfall was evaluated. From projected climate change data extracted from the Royal Netherlands Meteorological Institute (KNMI), future wind velocity and rainfall results can be derived using the Gumbel distribution method. Therefore, future building code can be designed based on these results in the Netherlands. A similar approach based on the Gumbel distribution method used in the Netherlands to find out future climatic change will be applied to Singapore. Using the method, current climate data will be extracted from the Meteorological Service Singapore and the projected climate change data will be extracted from the Singapore’s Second National Climate Change Study. The future wind velocity and rainfall results can be derived and the future building code can be designed and calculated based on these results. In addition, future intensive studies in this area can be done in Singapore using this method from the Netherlands so that we can have a better idea on how the climate will be in the future.